2008
DOI: 10.1080/09687680701510042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-hydroxyoleic acid on the structural properties of biological and model plasma membranes

Abstract: This article maybe used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribution, re-selling, loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae and drug doses should be independently verified with primary sources. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…In turn, 2OHOA showed a highly increased antihypertensive action in genetically hypertensive rats ( 18 ). Moreover, reconstituted plasma membranes from these rats showed a clear shift of their biophysical properties toward a higher propensity to form H II phases, paralleled by a signifi cant increase in the level of unsaturated FAs ( 16 ). Although these results do not fi rmly establish the molecular mechanism of action of 2OHOA, they indicate that the observed alteration of biophysical membrane parameters in vitro also occurs in vivo and should have pharmacological relevance.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In turn, 2OHOA showed a highly increased antihypertensive action in genetically hypertensive rats ( 18 ). Moreover, reconstituted plasma membranes from these rats showed a clear shift of their biophysical properties toward a higher propensity to form H II phases, paralleled by a signifi cant increase in the level of unsaturated FAs ( 16 ). Although these results do not fi rmly establish the molecular mechanism of action of 2OHOA, they indicate that the observed alteration of biophysical membrane parameters in vitro also occurs in vivo and should have pharmacological relevance.…”
Section: Discussionmentioning
confidence: 94%
“…2-Hydroxyoleic acid (2OHOA), a synthetic derivative of the naturally occurring oleic acid, induced the formation of H II structures in model membranes ( 15 ). In vivo, this observation was paralleled by an alteration of the membrane lipid composition which was related to the observed increase of G proteins in the plasma membrane of 2OHOA-treated animals ( 12,16 ). Moreover, 2OHOA showed a strongly enhanced antihypertensive action in this animal model of hypertension ( 17,18 ), thus demonstrating the viability of this new pharmacological approach.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 88%
“…17 Multilamellar lipid vesicles, 15% (wt/wt) with total lipid extracts, were prepared in 10 mmol/L of HEPES, 100 mmol/L of NaCl, and 1 mmol/L of EDTA (pH 7.4; HEPES buffer). 12 Lipid mixtures were hydrated, thoroughly homogenized with a pestle-type minihomogenizer (Sigma), and vortexed until a homogeneous mixture was obtained. Then, the suspensions were submitted to 5 temperature cycles (heated up to 70°C and cooled down to 4°C).…”
Section: Erythrocyte Model Membrane Preparationmentioning
confidence: 99%
“…8 -10 Changes in membrane lipid composition of hypertensive subjects have been associated with alterations in the transmembrane fluxes of Na ϩ and K ϩ , including Na ϩ -Li ϩ countertransport, which is a marker of essential hypertension, 10,11 and in cell signaling proteins that participate in the control of blood pressure. 12 On the other hand, it has been reported that dietary lipids have an effect on membrane lipid composition and cell signaling proteins. 4,5,12 Considering that changes in the dietary lipid composition yield to variations in the biophysical properties of the plasma membrane, it is likely that cellular functional changes could result from alterations in the structure of the lipid membrane properties influenced by the diet.…”
mentioning
confidence: 99%
See 1 more Smart Citation